Novel primers improve species delimitation in Cercospora - Mounes Bakhshi; Mahdi Arzanlou; Asadollah Babai-ahari; Johannes Z. Groenewald; Pedro W. Crous (IMA Fungus)
Abstract The genus Cercospora includes many important plant pathogens that are commonly associated with leaf spot diseases on a wide range of cultivated and wild plant species. Due to the lack of useful morphological features and high levels of intraspecific variation, host plant association has long been a decisive criterion for species delimitation in Cercospora. Because several taxa have broader host ranges, reliance on host data in Cercospora taxonomy has proven problematic. Recent studies have revealed multi-gene DNA sequence data to be highly informative for species identification in Cercospora, especially when used in a concatenated alignment. In spite of this approach, however, several species complexes remained unresolved as no single gene proved informative enough to act as DNA barcoding locus for the genus. Therefore, the aims of the present study were firstly to improve species delimitation in the genus Cercospora by testing additional genes and primers on a broad set of species, and secondly to find the best DNA barcoding gene(s) for species delimitation. Novel primers were developed for tub2 and rpb2 to supplement previously published primers for these loci. To this end, 145 Cercospora isolates from the Iranian mycobiota together with 25 additional reference isolates preserved in the Westerdijk Fungal Biodiversity Institute were subjected to an eight-gene (ITS, tef1, actA, cmdA, his3, tub2, rpb2 and gapdh) analysis. Results from this study provided new insights into DNA barcoding in Cercospora, and revealed gapdh to be a promising gene for species delimitation when supplemented with cmdA, tef1 and tub2. The robust eight-gene phylogeny revealed several novel clades within the existing Cercospora species complexes, such as C. apii, C. armoraciae, C. beticola, C. cf. flagellaris and Cercospora sp. G. The C. apii s. lat. isolates are distributed over three clades, namely C. apii s. str, C. plantaginis and C. uwebrauniana sp. nov. The C. armoraciae s. lat. isolates are distributed over two clades, C. armoraciae s. str. and C. bizzozeriana. The C. beticola s. lat. isolates are distributed over two clades, namely C. beticola s. str. and C. gamsiana, which is newly described.